Haematological profile of dengue fever - Tahlan, Anita; Bhattacharya, Amrita; Singla, Nidhi; Singh, Ram (International Journal of Research in Medical Sciences, 2017)
Background: Dengue is a viral illness that is increasingly becoming endemic in India. This study aimed to study the haematological profile of patients diagnosed with dengue infection in a tertiary care hospital. Methods: 89 patients suspected of having dengue illness were followed. Out of which those confirmed by positive serology were followed and studied in detail (n=46). Results: Common clinical symptoms were fever, vomiting, and abdominal pain. Common haematological abnormalities were thrombocytopenia and leucopoenia. All patients improved clinically with improvement of biochemical and hematological parameters. None of the patients died in this series. Conclusions: Dengue Fever continues to be a significant health problem especially in Northern region of India. A sharp vigilance is required by concerned authorities to prevent and minimize any future outbreak. It is extremely important to implement and maintain an effective, sustainable and community based disease prevention program.